2021
DOI: 10.1108/jsm-03-2021-0096
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: When service technologies and human experiences intersect

Abstract: Purpose This paper aims to identify future research opportunities that address human–technology service interactions. Design/methodology/approach This editorial is based on the author’s personal reflections and conceptualizations of ideas from past previous research and theory. Findings The authors identify three opportunities for further research on technology and humanity: service technology and social interaction and service technology and societal prosperity. Research limitations/implications Service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…However, past studies have presented a diversity of findings regarding this perspective (Rosenbaum and Russell-Bennett, 2021;Ok et al, 2007). For example, some studies have shown a positive impact of SR on customer behavior (Jung and Seock, 2017), while other findings have been negative (Kim et al, 2022).…”
Section: Mediating Role Of Service Recoverymentioning
confidence: 99%
“…However, past studies have presented a diversity of findings regarding this perspective (Rosenbaum and Russell-Bennett, 2021;Ok et al, 2007). For example, some studies have shown a positive impact of SR on customer behavior (Jung and Seock, 2017), while other findings have been negative (Kim et al, 2022).…”
Section: Mediating Role Of Service Recoverymentioning
confidence: 99%
“…Specifically in services marketing research, De Keyser et al (2019) and Čaić, Mahr and Oderkerken-Schröder (2019) show that some emerging technologies, such as robots and wearable devices, directly impact the servicescape and, thereby, consumer well-being. These ideas resonate with Rosenbaum and Russell-Bennett’s (2021) work by emphasizing the role of HET in promoting better human experiences in the context of services. However, most of the technologies portrayed in their study work as wearable tools and not as part of human biology, as preconized by transhumanism principles.…”
Section: Introductionmentioning
confidence: 81%
“…In presenting the consumption of HET as a means to achieve a “harder, better, faster, stronger” human biological condition and, therefore, supposedly super well-being, we directly engage with and contribute to Rosenbaum and Russell-Bennett’s (2021) call for research on the intersection of technologies and human experiences in service contexts. We do this by offering a unique perspective that is thus far largely unexplored in services marketing research.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, this is one of the first papers in the services marketing discipline that investigates the promises and perils of those transhumanism ideals and HETs and discusses the potential of HETs in doing great good or bad. As more research on the technology-services interaction and the role of various technologies on well-being topics is encouraged (Rosenbaum and Russell-Bennett, 2021), highlighting the concept of transhumanism in this paper is the right step in advancing the technology-related service research. Furthermore, this paper also discusses its proposed framework in the context of bioethics and thus invites service scholars to collaborate with colleagues from the medicine and ethics fields to understand broader applications of transhumanism and HETs.…”
Section: The Articles In the Special Issuementioning
confidence: 99%